2022
DOI: 10.3390/fractalfract6020111
|View full text |Cite
|
Sign up to set email alerts
|

Electronically Controlled Power-Law Filters Realizations

Abstract: A generalized structure that is capable of implementing power-law filters derived from 1st and 2nd-order mother filter functions is presented in this work. This is achieved thanks to the employment of Operational Transconductance Amplifiers (OTAs) as active elements, because of the electronic tuning capability of their transconductance parameter. Appropriate design examples are provided and the performance of the introduced structure is evaluated through simulation results using the Cadence Integrated Circuits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…It is demonstrated that the PLFs reported in [20][21][22][23] are also a small subset of the class of filters proposed in this work; 2.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…It is demonstrated that the PLFs reported in [20][21][22][23] are also a small subset of the class of filters proposed in this work; 2.…”
Section: Introductionmentioning
confidence: 78%
“…Two FO elements-based band-stop filter of the form (s p + k 1 s q + k 2 )/(s p + k 3 s q + k 2 ), where, p = 1 + β 1 + β 2 , q = 1 + β 2 , and β 1 , β 2 ∈ (0, 1), was presented in [29], which is also unlike the proposed fractional-order band-stop filter (FBSF) model. Note that the transfer function of the PLF reported in [20][21][22][23] can be obtained from (4) by setting α = 1. Therefore, the proposed FO filter transfer function also provides a further generalization of the PLF models.…”
Section: Phasementioning
confidence: 99%
See 2 more Smart Citations
“…Here, denotes the mother function of the standard filter. The methods efficient for approximating power-law filters are either frequency response curve fitting or padé approximations [ 33 ]. Single and double dispersion impedance models were represented by power-law filters in [ 34 ].…”
Section: Introductionmentioning
confidence: 99%